Analisis Pengaruh Impor Beras, Inflasi, Dan Luas Lahan Sawah Terhadap Nilai Tukar Petani di Indonesia Tahun 2003-2017 - Dhimas Khoiri; Ida Nuraini (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2022)
The purpose of this study is to analyze the factors that affect the Farmer Exchange Rate (NTP). There are three independent variables in this study, namely rice imports, inflation, and rice field area. This research uses secondary data which comes from the BPS website and Ministry of Trade. The data analysis technique used is the multiple linear regression method and using the E-views 9 analysis tool. The results of this research are that the rice import variable and rice field area have a significant effect on the farmer exchange rate, while the inflation variable does not have a significant effect on the farmer exchange rate.